PENGEMBANGAN VIDEO ANIMASI BERBASIS ISU LINGKUNGAN LOKAL PADA PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Triannisa, Sisca; Erlisnawati, Erlisnawati; Guslinda, Guslinda (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This research aims to address the limited availability of contextual digital learning media in elementary schools, particularly the absence of animated videos that integrate local environmental issues relevant to student’s daily lives, by developing a valid and practical animated video for fifth-grade natural and social science learning. The animated video based on local environmental issues was developed using the Research and Development (R&D) method with Thiagarajan’s 4D model. It passed the validation stage by material experts, media experts, and language experts, achieving a final percentage score of 92% (very valid). Then, the practicality test with teachers and students resulted in a final percentage score of 84% (very practical). The development of this animated video not only provides an effective and contextual learning resource for teachers, but also supports students’ conceptual understanding and environmental awareness, demonstrating its potential for broader application in natural and social science learning.